Schreiben lehren: Eine fach- und diskurssensible Fortbildung für Lehrende (2) - Scharlau, Ingrid; Karsten, Andrea (Neues Handbuch Hochschullehre. 86. Ergänzungslieferung)

Schreiben lehren: Eine fach- und diskurssensible Fortbildung für Lehrende (1) - Scharlau, Ingrid; Karsten, Andrea (Neues Handbuch Hochschullehre. 85. Ergänzungslieferung)

Quantitative Explanation as a Tight Coupling of Data, Model, and Theory - Krüger, Alexander; Tünnermann, Jan; Rohlfing, Katharina; Scharlau, Ingrid (Archives of Data Science, Series A)
What does it mean to explain data patterns? Cognitive psychologists and other scientists face this question when observable phenomena have to be explained in theoretical terms. Frequentist null-hypothesis testing – one prominent approach in psychology – controls error rates. Machine learning – an alternative prominent outside of, but not yet inside psychology – focuses on precise predictions. However, both alternatives often provide little insight into the data. We propose a combination of formal modeling and Bayesian statistical inference to ground explanations in data analysis. We support this approach by reference to philosophy of science and discussions of the current methods crisis in several empirical sciences and illustrate it with an example from visual attention research.

Einheitlich, doch nicht ganz: Zur Fachdidaktik des Hochschul- und Schulfachs Psychologie. - Scharlau, Ingrid (Psychologieunterricht)
Keywords: Unterrichtsfach Psychologie

Schreiben im Psychologiestudium - Scharlau, Ingrid; Klingsieck, Katrin

Schreiben im Psychologiestudium - Klingsieck, Katrin B.; Scharlau, Ingrid

Videokonfrontation als Methode für die angewandte Schreibforschung. Zwischen Investigation und Intervention - Karsten, Andrea (Qualitative Methoden in der Schreibforschung)

Zwei Varianten qualitativer Textanalyse zur Identifikation von Stimme(n) in Texten - Karsten, Andrea; Stock, Ingrid (Qualitative Methoden in der Schreibforschung)

Measuring and modeling salience with the theory of visual attention. - Krüger, Alexander; Tünnermann, Jan; Scharlau, Ingrid (Attention, Perception, & Psychophysics)
For almost three decades, the theory of visual attention (TVA) has been successful in mathematically describing and explaining a wide variety of phenomena in visual selection and recognition with high quantitative precision. Interestingly, the influence of feature contrast on attention has been included in TVA only recently, although it has been extensively studied outside the TVA framework. The present approach further develops this extension of TVA’s scope by measuring and modeling salience. An empirical measure of salience is achieved by linking different (orientation and luminance) contrasts to a TVA parameter. In the modeling part, the function relating feature contrasts to salience is described mathematically and tested against alternatives by Bayesian model comparison. This model comparison reveals that the power function is an appropriate model of salience growth in the dimensions of orientation and luminance contrast. Furthermore, if contrasts from the two dimensions are comb
Keywords: Salience; Visual attention; Bayesian inference; Theory of visual attention; Computational modeling; Inference; Object Recognition; Theories; Visual Perception; Visual Attention; Luminance; Perceptual Orientation; Statistical Probability; Stimulus Salience; Computational Modeling

Measuring Attention and Visual Processing Speed by Model-based Analysis of Temporal-order Judgments - Tünnermann, Jan; Krüger, Alexander; Scharlau, Ingrid (Journal of Visualized Experiments)
This protocol describes how to conduct temporal-order experiments to measure visual processing speed and the attentional resource distribution. The proposed method is based on a new and synergistic combination of three components: the temporal-order judgments (TOJ) paradigm, Bundesen's Theory of Visual Attention (TVA), and a hierarchical Bayesian estimation framework. The method provides readily interpretable parameters, which are supported by the theoretical and neurophysiological underpinnings of TVA. Using TOJs, TVA-based estimates can be obtained for a broad range of stimuli, whereas traditional paradigms used with TVA are mainly limited to letters and digits. Finally, the meaningful parameters of the proposed model allow for the establishment of a hierarchical Bayesian model. Such a statistical model allows assessing results in one coherent analysis both on the subject and the group level. To demonstrate the feasibility and versatility of this new approach, three experiments are reported with attention manipulations in synthetic pop-out displays, natural images, and a cued letter-report paradigm.

Gegen das weibliche Cooling-out in der Wissenschaft. Mentoring für Frauen in der Promotionsphase - Steinhausen, Julia; Scharlau, Ingrid (Praxishandbuch Mentoring in der Wissenschaft)

Diese Linie sollte man verlängern: Zum Verhältnis der Hochschuldidaktik zu den Fächern - Scharlau, Ingrid (Zwischen Wissenschaftsforschung, Wissenschaftspropädeutik und Hochschulpolitik. Hochschuldidaktik als lebendige Werkstatt. Festschrift für Ludwig Huber zum 80. Geburtstag)

Zugänge zur Erfassung der Schreibkompetenzen von Studierenden in lehrnahen Untersuchungen: Ein Methodenkompass - Scharlau, Ingrid; Golombek, Christiane; Klingsieck, Katrin B. (die hochschullehre)
Ziel dieses Beitrags ist die Vorstellung und Diskussion unterschiedlicher Methoden zur Erfassung von hochschulischen Lernprozessen. Den konzeptuellen Rahmen dafür bietet das Scholarship of Teaching and Learning (SoTL). Am Beispiel von Schreibkompetenzen werden Analysen von Textproben, Selbsteinschätzungen per Fragebogen und Interview, Protokolle lauten Denkens und standardisierte Testverfahren vorgestellt. Die Vor- und Nachteile jeder Methode werden anhand exemplarischer Fragestellungen diskutiert. Abschließend reflektiert der Beitrag die Frage, wie SoTL von Überlegungen aus mixed-methods-Ansätzen profitieren kann.

Schreiben eine Stimme geben. Über die Beziehung von lautem Sprechen und Schreiben im Schreibprozess - Lohmeier, Yvonne; Karsten, Andrea (JoSch – Journal der Schreibberatung)
Keywords: Schreibberatung; Schreibdidaktik; Schreibprozess; Sprache

Fast and conspicuous? Quantifying salience with the theory of visual attention. - Krüger, Alexander; Tünnermann, Jan; Scharlau, Ingrid (Advances in Cognitive Psychology)
Particular differences between an object and its surrounding cause salience, guide attention, and improve performance in various tasks. While much research has been dedicated to identifying which feature dimensions contribute to salience, much less regard has been paid to the quantitative strength of the salience caused by feature differences. Only a few studies systematically related salience effects to a common salience measure, and they are partly outdated in the light of new findings on the time course of salience effects. We propose Bundesen’s Theory of Visual Attention (TV A) as a theoretical basis for measuring salience and introduce an empirical and modeling approach to link this theory to data retrieved from temporal-order judgments. With this procedure, TV A becomes applicable to a broad range of salience-related stimulus material. Three experiments with orientation pop-out displays demonstrate the feasibility of the method. A 4th experiment substantiates its applicability t
Keywords: salience; visual attention; Bayesian inference; theory of visual attention; computational modeling; Visual Attention; Computational Modeling; Inference; Judgment; Statistical Probability

Peripheral visual cues: Their fate in processing and effects on attention and temporal-order perception. - Tünnermann, Jan; Scharlau, Ingrid (Frontiers in Psychology)
Peripheral visual cues lead to large shifts in psychometric distributions of temporal-order judgments. In one view, such shifts are attributed to attention speeding up processing of the cued stimulus, so-called prior entry. However, sometimes these shifts are so large that it is unlikely that they are caused by attention alone. Here we tested the prevalent alternative explanation that the cue is sometimes confused with the target on a perceptual level, bolstering the shift of the psychometric function. We applied a novel model of cued temporal-order judgments, derived from Bundesen’s Theory of Visual Attention.We found that cue–target confusions indeed contribute to shifting psychometric functions. However, cue-induced changes in the processing rates of the target stimuli play an important role, too. At smaller cueing intervals, the cue increased the processing speed of the target. At larger intervals, inhibition of return was predominant. Earlier studies of cued TOJs were insensitive
Keywords: cueing; temporal-order judgements; theory of visual attention (TVA); peripheral cue; processing speed; stimulus encoding; prior entry; Attention; Cues; Face Perception; Judgment

Writer’s overload: A multifaceted concept and its clarification. - Scharlau, Ingrid; Karsten, Andrea; Klingsieck, Katrin B. (die hochschullehre)
Many problems student writers are faced with can be understood as writer’s overload, the inability to tackle the high and complex concurrent demands of the writing process. In the present paper, we spell out multiple notions of writer’s overload from the perspectives of cognitive, educational, and sociocultural psychology in order to provide faculty from all disciplines with some background to understand their students’ writing problems. Starting from the Scholarship of Teaching and Learning approach, our aim is to provide teachers with ideas on how they can change crucial aspects of learning activities in their classes and of their teaching practice and study how this affects learning and writing in order to advance the teaching of writing.
Keywords: SoTL; student writing; writer's overload; writing block

(Un)diszipliniertes Schreiben? Schreiben lehren und lernen im Studium und in den Fächern an der Leuphana Universität - Heß, Christiane; Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

"Das zu riskieren, ist schon eine große Tat": Ludwig Huber im Gespräch mit Ingrid Scharlau - Huber, Ludwig; Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

Attention, awareness, discipline, and effort: Die Liberal Arts und ein College in Deutschland - Beck, Karin; Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)